Electrocatalytic Disproportionation of Nitric Oxide Toward Efficient Nitrogen Fixation (Adv. Energy Mater. 14/2023). Issue 14 (13th April 2023) - Wu, Angjian; Lv, Jiabao; Xuan, Xiaoxu; Zhang, Jinhe; Cao, Ang; Wang, Mengjie; Wu, Xiao‐Yu; Liu, Qian; Zhong, Yunhao; Sun, Wei; Ye, Qiulin; Peng, Yaqi; et al.
Abstract : Nitrogen Fixation In article number 2204231, Angjian Wu, Hao Bin Wu, Jianhua Yan, and co‐workers achieve electrocatalytic disproportionation of nitric oxide in a bipolar membrane based electrolysis system with decoupled acid–base electrolytes, which aims for efficient nitrogen fixation via coupling the cathodic NO reduction reaction with the anodic NO electrooxidation simultaneously.